Turn it up and open the window: On the rebound effects in residential heating - Cecile Hediger; Mehdi Farsi; Sylvain Weber (University of Neuchâtel, Institute of Economic Research (IRENE), 2017)
This paper investigates how households respond to efficiency improvement of their heating system. Micro-level rebound effects are estimated using a survey with an innovative choice experiment based on the stated preference approach. The experiment design allows to identify the direct and indirect rebound effects as well as their possible trade-offs at the household level. A series of easy discrete choices have been designed to prime respondents and make them think about potential actions impacting their heating service demand. Answers to these discrete choices are moreover used to cross-validate the quantitative results. Overall, we find relatively low direct rebound effects. However, after considering indirect rebound effects calculated as embodied primary energy, we estimate a total rebound of more than one third. The econometric analysis points to substantial variation across individuals that is only partly explained by observed characteristics. The results are consistent with the conjunction that heating is a basic need that calls for little rebound in high-income groups.
Keywords: D12; Q41; Q47; R22; 330; Rebound effects; energy efficiency; residential heating